Adverse events of interest following influenza vaccination, a comparison of cell culture-based with egg-based alternatives: English sentinel network annual report paper 2019/20 - de Lusignan, S; Tsang, RSM; Amirthalingam, G; Akinyemi, O; Sherlock, J; Tripathy, M; Deeks, A; Ferreira, F; Howsam, G; Hobbs, FDR; Joy, M (Elsevier, 2021)
Background: The cell-based quadrivalent influenza vaccine (QIVc) is now offered as an alternative to egg-based quadrivalent (QIVe) and adjuvanted trivalent (aTIV) influenza vaccines in the UK. While post-licensure studies show non-inferiority of cell-based vaccines, it is not known how its safety profile compares to other types of vaccines in real-world use.